(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2026)
Alpinia galanga (Kaluwala) is frequently used in Sri Lankan Indigenous Medicine to treat skin infections, inflammatory disorders, and respiratory conditions. Traditionally, healers employ cold-water preparations of the rhizome, but these methods have limited scientific validation. Therefore, this study was conducted to assess the antibacterial and antifungal properties of an aqueous rhizome extract of A. galanga prepared using traditional methods. Shade-dried rhizomes were soaked in sterile cold water, filtered, and analyzed for yield and phytochemical composition. Antimicrobial activity was evaluated using the agar-well diffusion technique against Streptococcus pneumoniae (ATCC 12386), Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), methicillin-resistant Staphylococcus aureus (MRSA), and Candida albicans (ATCC 10231). Amoxicillin and fluconazole were used as positive controls. Phytochemical analysis revealed the presence of alkaloids, flavonoids, tannins, saponins, glycosides, and phenolic compounds. The extract inhibited the growth of all tested bacteria, including MRSA, but showed no activity against C. albicans. The largest inhibition zones were recorded for S. aureus (14.3 ± 0.6 mm), followed by S. pneumoniae (12.4 ± 0.5 mm), MRSA (11.8 ± 0.5 mm), and E. coli (10.2 ± 0.4 mm). Conclusion: The aqueous rhizome extract of A. galanga exhibits broad-spectrum antibacterial activity, supporting its traditional use for infected skin lesions. Further pharmacological, phytochemical, and formulation studies are warranted.